Peptic Ulcer in Rheumatoid Arthritis - Saku, Yoshihiko; Chihiro, Kimura; Morita, Shinji; Nagata, Hironobu; Tabe, Ryuji (Orthopedics & Traumatology, 1994)
It is well known that peptic ulcer occurs frequently in patients with rheumatoid arthritis (RA). To elucidate risk factors of peptic ulcer in RA, we studied 434 cases of definite and classical RA. The incidence (8.5%) of peptic ulcer in this study was significantly higher than that (1.8%) previorsly reported by mass survey (P<0.001). Risk factors of peptic ulcer in RA patients were aging (50<), longer disease duration and treatment with many non-steroidal anti-inflammatory drugs (NSAIDs). We could not find a relationship between incidence of peptic ulcer to treatment with steroidal drugs. We should pay careful attention to peptic ulcer in RA patients who have these risk factors.